PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP PENGGUNAAN PINJAMAN ONLINE DENGAN PERILAKU KONSUMTIF SEBAGAI VARIABEL MEDIASI - Dewi Firdaus, Taufiq Akbar; Tiswiyanti, Wiwik; Gowon, Muhammad (Komunitas Manajemen Kompetitif, 2025)
In the era of rapid technological advancement and digitalization, access to financial services has become increasingly easy. This study aims to examine the effects of financial literacy and risk perception on the use of online lending and consumptive behavior, as well as the effect of consumptive behavior on online lending usage, and its mediating role between financial literacy, risk perception, and online lending. This research adopts a quantitative approach using a survey method. Data were collected through a Likert-scale questionnaire (1–5), with 271 active students from the Faculty of Economics and Business, Universitas Jambi, selected using purposive sampling. Data analysis was conducted using SEM-PLS with SmartPLS 4 software. The results indicate that financial literacy and risk perception have a negative and significant effect on both consumptive behavior and online lending usage, while consumptive behavior has a positive and significant effect on online lending usage. Furthermore, consumptive behavior partially mediates the relationship between financial literacy and risk perception on the use of online lending. Keywords: Financial Literacy, Perceived Risk, Online Loans, Consumtive Behavior